Revolutionary recognition - Gunn, Richard 1947- (Bloomsbury Academic, 2021)
"The book is a major contribution to contemporary political theory, arguing that human emancipation is only possible in a society characterized by 'mutual recognition', understood in the Hegelian sense. In present-day political theory, 'recognition' is generally associated with reformist scenarios - seen as a way of legitimating social-democratic institutions or validating identity politics. Gunn and Wilding undertake a wide-ranging critique of these understandings of recognition, especially those of Charles Taylor and Axel Honneth, and argue, via Hegel and Marx, for mutual recognition's revolutionary (not reformist) character. Mutual recognition, they contend, can and should become the rallying cry of the Left"--
Keywords: Hegel, Georg Wilhelm Friedrich -- 1770-1831; Marx, Karl -- 1818-1883; Anerkennung; Politische Theorie; Political participation / Philosophy; Recognition (Philosophy) / Political aspects; Right and left (Political science); Electronic books